Análise do processo de gestão da informação em Unidades Básicas de Saúde do município de Campina Grande/PB - Vasconcelos, Daniel Henriques (2023)
This research presents an analysis of the Information Management process in Basic Health Units which are characterized by having a set of health actions, both at the individual and collective level, covering promotion, health protection, prevention of illnesses, diagnosis, treatment, rehabilitation, harm reduction and health maintenance with the aim of developing comprehensive care that positively impacts the health situation of communities. First of all, information must be considered an essential resource for any health service and must, therefore, be conceived as fundamental for the full success of therapeutic processes and for decision-making related to public policies in this area. The general objective was to analyze the Information Management process in Basic Health Units in the Municipality of Campina Grande/PB and as specific objectives, seek to identify Information Management actions and practices in accordance with the model proposed by Chun Wei Choo. Regarding the methodological dimension, the research is defined as exploratory and descriptive, with a qualitative approach, using case studies as research strategies. As for data collection instruments, they were used in document analysis, semi-structured interviews and focus groups, these data were detailed using the content analysis technique. The research results pointed to the existence of a deficient Information Management in all stages of the process, showing that there is no planning for information management in this context, which makes access and use of information difficult for its users. These results demonstrated, then, the need to implement all professional information management work in the basic health care service in the city of Campina Grande, aiming to use information strategically for the provision of health care, something essential for the planning, implementation and evaluation of health actions and services offered to the population.